2005
DOI: 10.1261/rna.2264806
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particles of the Ty3 retrotransposon assemble in association with P-body components

Abstract: Retroviruses and retrotransposons assemble intracellular immature core particles around a RNA genome, and nascent particles collect in association with membranes or as intracellular clusters. How and where genomic RNA are identified for retrovirus and retrotransposon assembly, and how translation and assembly processes are coordinated is poorly understood. To understand this process, the subcellular localization of Ty3 RNA and capsid proteins and virus-like particles was investigated. We demonstrate that mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(142 citation statements)
references
References 33 publications
3
139
0
Order By: Relevance
“…This observation suggests that Xrn1 either destabilizes other Ty1 regulatory RNAs or controls posttranscriptional steps during the transposition cycle. For instance, previous studies revealed a structural role of Xrn1 and P-body components in the assembly of gypsylike Ty3 VLPs (Beliakova-Bethell et al 2006). One could hypothesize that this function is conserved for the assembly process of Ty1 VLPs as well.…”
Section: Transcriptional Gene Silencingmentioning
confidence: 95%
“…This observation suggests that Xrn1 either destabilizes other Ty1 regulatory RNAs or controls posttranscriptional steps during the transposition cycle. For instance, previous studies revealed a structural role of Xrn1 and P-body components in the assembly of gypsylike Ty3 VLPs (Beliakova-Bethell et al 2006). One could hypothesize that this function is conserved for the assembly process of Ty1 VLPs as well.…”
Section: Transcriptional Gene Silencingmentioning
confidence: 95%
“…For example, recent results argue that the Ty3 retrotransposon in yeast may assemble its virus-like particles in association with P-bodies (Beliakova-Bethell et al 2006). This suggests that P-bodies may be important sites of specific steps in retrotransposon and viral life cycles that might then be modulated by miRNAs.…”
Section: Future Perspective and Issuesmentioning
confidence: 99%
“…Virus-like retrotransposon particle assembly takes place at or near P-bodies. As P-bodies are sites of mRNA degradation and storage (Brengues et al 2005), it has been suggested that P-body-associated translational repression promotes assembly of retrotransposon RNA into virus-like particles (Beliakova-Bethell et al 2006). Our observations suggest poly(A) tail length control as another aspect of this switch from translation to packaging of retrotransposon RNA.…”
Section: Mechanism Of Poly(a) Tail Length Regulationmentioning
confidence: 99%